Viabilidade de implantação de um sistema de tratamento e reuso das águas de lavagem de veículos: estudo de caso do lava-jato Lavatec em Tucuruí-PA - MUERZA, Thais dos Reis (2024)
The article shows a case study of the implementation of a sustainable car wash in the municipality of Tucuruí, whose objective is to present a methodology for the implementation of treatment systems and sustainable reuse of wastewater, analyzing the economic viability of the enterprise. For this, a literature review and field research was carried out to determine parameters that helped in the design of the system. From this, costs and cash flow were estimated to calculate financial variables that revolve around the system. The results show a return on investment (PayBack) period of approximately 7 months, with the Net Present Value (NPV) for six years of R$ R$ 76.078,79 and an Internal Rate of Return (IRR) 186%. These values demonstrate that sustainable car washes, for this case, are economically viable systems. Environmental viability was also confirmed, because the savings with water were 80%.